A Music-Related Quality of Life measure to guide music rehabilitation for adult CI users - Dritsakis, Giorgos; van Besouw, Rachel M.; Kitterick, Pádraig T.; Verschuur, Carl A. (American Speech-Language-Hearing Association, 2017)
Purpose: A music-related quality of life (MuRQoL) questionnaire was developed for the evaluation of music rehabilitation for adult cochlear implant (CI) users. The present studies were aimed at refinement and validation. Method: Twenty-four experts reviewed the MuRQoL items for face validity. A refined version was completed by 147 adult CI users and psychometric techniques were used for item selection, assessment of reliability and definition of the factor structure. The same participants completed the Short Form Health Survey for construct validation. MuRQoL responses from 68 CI users were compared with those of a matched group of normal-hearing (NH) adults. Results: Eighteen items measuring music perception & engagement and 18 items measuring their importance were selected; they grouped together into two domains. The final questionnaire has high internal consistency and repeatability. Significant differences between CI users and NH adults and a correlation between music engagement and quality of life (QoL) support construct validity. Scores of music perception & engagement and importance for the 18 items can be combined to assess the impact of music on the QoL. Conclusion: The MuRQoL questionnaire is a reliable and valid measure of self-reported music perception, engagement and their importance for adult CI users with potential to guide music aural rehabilitation.